PENDEKATAN FUNGSI POLYNOMIAL DARI BENDA PUTAR DENGAN METODE ELIMINASI GAUSS JORDAN - Ulul Azmi; Rita Yuliastuti; Kresna Oktafianto (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2016)
In calculus, integral operation is usually used to calculate a wide or volume of an object. But in reality there is a lot of object that the function is still unknown while in integral we need to it to be calculated. In this paper we proposed an approach to get the mathematic function of an object based on its shape. Actually with a whole data from that object we can use elimination Gauss Jordan to get a function, but that function is uncertainly able to generate the desired graph that similar to the object. A graph from non-linier function usually undergoing some change at some point, which is at extreme point and at turn point. With those point as a new limitation point we can get some new function that generate different or similar graph from each other. From those graph we compare them with the object shape and analyzing them to decide which one is the most approaching the object shape. In this paper we get the conclusion that in order to get the desired graph we need to test function from all three type of data then compare them to the real object shape.